Biznes jako wojna. Retoryka wojenna w tytułach prasy ekonomicznej - Kochan, Marek (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2016)
The topic of this article is the usage of the metaphor of war in the headlines of articles from "Ekonomia& Rynek" ("Economy&Market"), a division of the Rzeczpospolita daily, devoted to business issues. In order to establish the frame of the analysis, the author discusses the cognitive functions of metaphors (using G. Lakoff and M. Johnson’s study "Metaphors we live" by and other works devoted to the subject), the functions of the headlines in relation to the text and the usage of the rhetoric of war in business language. The majority of the paper is dedicated to a detailed analysis of headlines using the metaphor of war found in the examined sample (a total of 34 in 146 editions of the "Ekonomia&Rynek" section). In the article, the main elements of these metaphors are described: commonly used words, parties to the conflict, the nature of the conflict, the temporal dimension etc. In the final section of the text the author explores the issue of the potential results of the usage of metaphor of war: both for the readers and the institutions engaged in the conflicts.